2000
DOI: 10.1128/jvi.74.21.10212-10216.2000
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Rabies Virus P Protein with the LC8 Dynein Light Chain

Abstract: The rabies virus P protein is involved in viral transcription and replication but its precise function is not clear. We investigated the role of P (CVS strain) by searching for cellular partners by using a two-hybrid screening of a PC12 cDNA library. We isolated a cDNA encoding a 10-kDa dynein light chain (LC8). LC8 is a component of cytoplasmic dynein involved in the minus end-directed movement of organelles along microtubules. We confirmed that this molecule interacts with P by coimmunoprecipitation in infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
215
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(220 citation statements)
references
References 40 publications
2
215
0
3
Order By: Relevance
“…RPP has also been shown to interact with the DLC LC8 via a DLC-AS containing an archetypal LC8 association motif (KSTQT) in the region 139 -174 using the yeast two-hybrid system (Raux et al, 2000;Poisson et al, 2001). A role in retrograde trafficking of RPP associated with dynein on MT has been suggested (Raux et al, 2000) but evidence for this is lacking, and no direct effect of the DLC-AS on transport into the nucleus has been described.…”
Section: The Rpp Dlc-as Mediates Association With Lc8 In Vivo and Enhmentioning
confidence: 99%
See 3 more Smart Citations
“…RPP has also been shown to interact with the DLC LC8 via a DLC-AS containing an archetypal LC8 association motif (KSTQT) in the region 139 -174 using the yeast two-hybrid system (Raux et al, 2000;Poisson et al, 2001). A role in retrograde trafficking of RPP associated with dynein on MT has been suggested (Raux et al, 2000) but evidence for this is lacking, and no direct effect of the DLC-AS on transport into the nucleus has been described.…”
Section: The Rpp Dlc-as Mediates Association With Lc8 In Vivo and Enhmentioning
confidence: 99%
“…Although the sequences responsible for p53, PTHrP, and Rb interaction with MTs/dynein remain largely undefined, short sequences from several other proteins have been identified, using the yeast two-hybrid system and proteomics approaches, which confer interaction with the dynein light chains (DLC), LC8 and Tctex-1. These sequences variously include the consensus motifs KSTQT (single letter amino acid code) and GIQVD for LC8, as well as less well-defined motifs for Tctex-1 interaction, including SKCSR (Raux et al, 2000;Alonso et al, 2001;Poisson et al, 2001;RodriguezCrespo et al, 2001;Mueller et al, 2002;Martinez-Moreno et al, 2003;Sugai et al, 2003;Lo et al, 2005). DLC-ASs have been suggested to mediate cargo association with dynein motor complexes to effect nuclear targeting, so that they could potentially be exploited for delivery of therapeutics to This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E07-01-0030) on June 13, 2007. cell nuclei (Cohen et al, 2005;Mastrobattista et al, 2006a,b); however, this has never been directly demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minor variations in G protein such as substitution of arginine at position 333 affects neuroinvasiveness by use of different neuronal pathways [68]. Interaction between the phosphoprotein of rabies virus, and LC8-the cytoplasmic dynein light chain that regulates microtubule-mediated transport-is implicated in viral transport [69][70][71]. However, mutant viruses with deletion in phosphoprotein encompassing LC8-interacting motif retained their neuroivasiveness and virulence [72].…”
Section: Viral Spread To the Cnsmentioning
confidence: 99%